Bilateral neovascular age-related macular degeneration: unilateral regression following endophthalmitis with persistent activity in the fellow eye. Issue 3 (24th March 2022) - Gaur, Sandhya; Singh, Deependra Vikram; Reddy, Raja Rami; Sharma, Ajay
Abstract : A woman in her 70s who was being followed up for neovascular age-related macular degeneration (nAMD) in both eyes for 2 years with recalcitrant choroidal neovascularisation (CNV) and had an episode of acute endophthalmitis in one eye was identified. After treatment of postinjection culture-negative right eye (RE) endophthalmitis with intravitreal vancomycin and tazobactam, the patient had complete regression of treatment-resistant CNV in RE to date with postinfection follow-up of 2 years. In contrast, the fellow eye continued showing activity in the choroidal neovascular membrane that required antivascular endothelial growth factor injections on a pro re nata basis to date. Prolonged regression of nAMD for 3 years in the affected eye and continued activity in the fellow eye support the hypothesis that inflammation accompanying endophthalmitis or the drugs used for the treatment can have a role in the regression of nAMD.